The Effect of Traditional Malting Technology Practiced by an Ethnic Community in Northern Uganda on In-Vitro Nutrient Bioavailability and Consumer Sensory Preference for Locally Formulated Complementary Food Formulae - Alowo, Docus; Muggaga, Christopher; Ongeng, Duncan (Food Science & Nutrition, 2018)
The occurrence of anti-nutritional constituents in plants is an important factor that negatively affects bioavailability of nutrients and effectiveness of plant-based foods in complementary feeding in rural areas in developing countries. However, proven methods that improve bioavailability of nutrients and tailored for application in processing complementary foods among rural communities are largely lacking. This study examined the efficacy of a traditional malting technology practiced by the Acholi ethnic community of northern Uganda to improve protein digestibility and bioavailability of iron and zinc from millet–sesame–soy composite containing 200, 300, and 550 kcal meant for complementary feeding of children aged 6–8, 9–12, and 13–23 years old, respectively. The technology involves washing and soaking of ingredients for 12 hr; malting ingredients individually for 48 hr with water changed after every 6 hr; and sun-drying malted ingredients for 72 hr. Results showed that the level of anti-nutritional factors significantly reduced (p ≤ 0.05) in all the composite formulae except the content of total phenolics in 200, tannins in 300 and 550 kcal, composite formula, respectively. In vitro protein digestibility significantly improved (p ≤ 0.05) in all the composite formulae except in the 200 kcal formula. Iron bioavailability significantly increased (p ≤ 0.05) in all the composite formulae except in the 550 kcal energy category. Improvement in zinc bioavailability was only observed in the 300 kcal formula. However, there were significant reductions (p ≤ 0.05) in the level of caregiver preferences for sensory properties and overall acceptability of the composites. These results demonstrate that the traditional malting technology has potential to improve nutrient bioavailability in plant-based foods but requires improvement in order to increase its efficacy and mitigate negative effects on sensory appeal.
Keywords: anti-nutritional factors, complementary food, nutrient bioavailability, sensory preference, traditional malting technology